Central administration of afzelin extracted from Ribes fasciculatum improves cognitive and memory function in a mouse model of dementia - So-Young Oh; Min Jun Jang; Yun-Hyeok Choi; Hongik Hwang; Hyewhon Rhim; Bonggi Lee; Chun Whan Choi; Min Soo Kim (Scientific Reports, 2021)
Abstract Neurodegenerative disorders are characterized by the decline of cognitive function and the progressive loss of memory. The dysfunctions of the cognitive and memory system are closely related to the decreases in brain-derived neurotrophic factor (BDNF) and cAMP response element-binding protein (CREB) signalings. Ribes fasciculatum, a medicinal plant grown in diverse countries, has been reported to pharmacological effects for autoimmune diseases and aging recently. Here we found that afzelin is a major compound in Ribes fasciculatum. To further examine its neuroprotective effect, the afzelin (100 ng/µl, three times a week) was administered into the third ventricle of the hypothalamus of C57BL/6 mice for one month and scopolamine was injected (i.p.) to these mice to impair cognition and memory before each behavior experiment. The electrophysiology to measure long-term potentiation and behavior tests for cognitive and memory functions were performed followed by investigating related molecular signaling pathways. Chronic administration of afzelin into the brain ameliorated synaptic plasticity and cognitive/memory behaviors in mice given scopolamine. Studies of mice’s hippocampi revealed that the response of afzelin was accountable for the restoration of the cholinergic systems and molecular signal transduction via CREB-BDNF pathways. In conclusion, the central administration of afzelin leads to improved neurocognitive and neuroprotective effects on synaptic plasticity and behaviors partly through the increase in CREB-BDNF signaling.